1991
DOI: 10.1002/tea.3660280103
|View full text |Cite
|
Sign up to set email alerts
|

Teacher awareness of student alternate conceptions about rotational motion and gravity

Abstract: Twenty high school physics teachers were interviewed to determine their awareness of student alternate conceptions in the areas of force and gravity. The teachers were also asked to indicate preferred teaching strategies dealing with alternate conceptions. Teacher predictions of student responses were compared to alternate conceptions held by 315 grade‐nine students and published findings from other research studies. Edmonton students were found to possess nearly every alternate conception identified in previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 32 publications
1
34
1
5
Order By: Relevance
“…However, the existence of these two misconceptions was neglected by most pre-service science teachers. Our findings support previous studies where teachers are found to have unawareness of students' misconceptions which they have learned (Berg & Brouwer, 1991;Hashweh, 1987). More explicitly, as another research reported, pre-service teachers tended to make incorrect judgments about students' likely misconceptions (Halim & Meerah, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the existence of these two misconceptions was neglected by most pre-service science teachers. Our findings support previous studies where teachers are found to have unawareness of students' misconceptions which they have learned (Berg & Brouwer, 1991;Hashweh, 1987). More explicitly, as another research reported, pre-service teachers tended to make incorrect judgments about students' likely misconceptions (Halim & Meerah, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Then, forward amendments about pre-service science teachers' knowledge of student learning difficulties should be put by expert teachers. As pointed out in the previous researches, teachers need to be made aware of the teaching strategies that cope with student learning difficulties (Berg & Brouwer, 1991) and instructional strategies to overcome student learning difficulties could significantly add to the evolution of preservice science teachers' PCK (Shulman, 1986 ;Halim & Meerah, 2002;Driel et al 1998; Demirdogen, Aydin, & Tarkin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Aydın-Güç, & Hacısalihoğlu-Karadeniz (2016), Berg & Brouwer (1991), Smith & Neale (1989) and Son (2006) concluded similar results. The Updated Secondary School Mathematics Teaching Program (MEB, 2013) anticipates that students make use of concrete experiences, intuitions, informal information that they have in their daily life in order to support conceptual learning.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 68%
“…Do teachers, however, hold the accepted scientific view of the force concept themselves and are they, in fact, aware of their students' alternative conceptual frameworks? Berg and Brouwer (1991) carried out a study on Canadian high school physics teachers awareness of students alternate conceptions about rotational motion and gravity. They found that the teachers were mainly unaware of students' alternate conceptions about gravity.…”
Section: Introductionmentioning
confidence: 99%